The impact of compact radio sources on their host galaxies: observations. Issue 1 (February 2016) - Tadhunter, C.
Abstract: I review the observational evidence that CSS/GPS radio sources have a significant impact on the evolution of their host galaxies, particularly on the kpc‐scales of the galaxy bulges. Starting with an overview of the observational evidence for jet‐cloud interactions and warm ionised outflows in CSS/GPS sources, I then consider the challenges involved in quantifying the feedback effect of the warm outflows in terms of their mass outflow rates and kinetic powers. For the best‐observed cases it is shown that the warm outflows may have a major negative feedback effect in the very central regions, but probably lack the power to heat and eject the full cool ISM contents of the host galaxies. In contrast, the recently‐discovered neutral and molecular outflows are more massive and powerful and therefore carry more destructive potential. However, the feedback effect of such outflows is not necessarily negative: there is now clear observational evidence that the molecular outflows are formed as the hot, compressed gas cools behind fast shocks driven into the ISM by the relativistic jets. The natural endpoint of this process is the formation of stars. Therefore, jet‐induced star formation may be a significant process in CSS/GPS radio galaxies. Finally, I discuss whether CSS/GPS sources are "imposters" in flux‐limited radio samples, due the flux boosting of the radio sources by strong jet‐cloud interactions in the early stages of radio source evolution. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)